"I Lost Myself": A Classical Idea of the Self. Issue 2 (3rd April 2017) - Shaoming, Chen
EDITOR'S ABSTRACT: This is a reflection on the notion of "self, " primarily on the basis of a story in the Zhuangzi in which the protagonist claims: "I lost myself." Chen first reiterates the grammatical differences between the uses of 吾 (wu) and 我 (wo), and continues with a reflection on their philosophical meaning. He argues that the notion of " wo " is more spatial, connected to the body, and distinguished from others; " wu " is more temporal, related to one's memory and self-understanding. The loss of " wo " by " wu " is a liberation from interpersonal tensions and the emphasis on one's body.